Treatment of Congenital Rectal Fistulae Associated with Imperforate Anus in Females - Waklu, A. K.; Tandon, R. K. (Indian Journal of Plastic Surgery, 1972)
The results of perineal proctoplasty in 10 cases of congenital low rectal fistulas associated with imperforate anus in female babies have been presented. The technique of perineal proctoplasty has been outlined with emphasis on the steps which ensure a good result.